Health Disparities Research Among Small Tribal Populations: Describing Appropriate Criteria for Aggregating Tribal Health Data - Van Dyke, Emily R. (Am J Epidemiol, 2016)
In response to community concerns, we used the Tribal Participatory Research framework in collaboration with 5 American-Indian communities in Washington, Idaho, and Montana to identify the appropriate criteria for aggregating health data on small tribes. Across tribal sites, 10 key informant interviews and 10 focus groups (n = 39) were conducted between July 2012 and April 2013. Using thematic analysis of focus group content, we identified 5 guiding criteria for aggregating tribal health data: geographic proximity, community type, environmental exposures, access to resources and services, and economic development. Preliminary findings were presented to focus group participants for validation at each site, and a culminating workshop with representatives from all 5 tribes verified our final results. Using this approach requires critical assessment of research questions and study designs by investigators and tribal leaders to determine when aggregation or stratification is appropriate and how to group data to yield robust results relevant to local concerns. At project inception, tribal leaders should be consulted regarding the validity of proposed groupings. After regular project updates, they should be consulted again to confirm that findings are appropriately contextualized for dissemination.